Constraining a Possible Variation of G with Type Ia Supernovae. (10th March 2014) - Mould, Jeremy; Uddin, Syed A.
Abstract: Astrophysical cosmology constrains the variation of Newton's Constant in a manner complementary to laboratory experiments, such as the celebrated lunar laser ranging campaign. Supernova cosmology is an example of the former and has attained campaign status, following planning by a Dark Energy Task Force in 2005. In this paper, we employ the full SNIa data set to the end of 2013 to set a limit on G variation. In our approach, we adopt the standard candle delineation of the redshift distance relation. We set an upper limit on its rate of change $|\dot{G}/G|$ of 0.1 parts per billion per year over 9 Gyrs. By contrast, lunar laser ranging tests variation of G over the last few decades. Conversely, one may adopt the laboratory result as a prior and constrain the effect of variable G in dark energy equation of state experiments to δ w < 0.02. We also examine the parameterisation G ~ 1 + z . Its short expansion age conflicts with the measured values of the expansion rate and the density in a flat Universe. In conclusion, supernova cosmology complements other experiments in limiting G variation. An important caveat is that it rests on the assumption that the same mass of 56 Ni is burned to create the standard candle regardless of redshift. These two quantities, f and G, where f is the Chandrasekhar mass fraction burned, are degenerate. Constraining f variation alone requires more understanding of the SNIa mechanism.